PENGARUH PEMANFAATAN SHAMPO EKSTRAK GAMBIR TERHADAP PERAWATAN KULIT KEPALA BERKETOMBE - Kasturi, Yusnia; Rahmiati, Rahmiati; Rosalina, Linda (Journal of Home Economics and Tourism, 2017)
Dandruff is a scalp disorder usualy occur at the age of 20-50 years old. Dandruff can lead to scalp scor, bad odor hair loss. This study aimed to analyze the effect of Gambir extract shampoo to treat dandruff is divided into two groups: control group (X0) with the treatment without using Extract Shampoo Gambir, and the experimental group (X1) with treatment using Gambir Shampoo Extract which performed in 1 times a day, the indicator is amount of dandruff.This study used a quasi-experimental methods with (Non Equivalent Control Group Design). The object of this study is people female with dandruff sample taken through purposive sampling technique. Total samples of are six people, with 20-50 years old with type dandruff scalp. Data collected from this study are primary data which obtained directly from the sample. Data analysis technique used is descriptive analysis and hypothesis testing using t test (independent samples t test).Based on the analysis of the control group (X0) showed no signifcant change until last treatment (8) in the experiment group (XI) showed progress until the last treatment. Then homogeneity testing has been done it acquired two data have the same variance (homogeneous), therefore the value of t referenced in testing the hypothesis is t on Equal variances assumed. The above data shows that tcount is equal to (12.176), while the value t table for provisions df 4 at a significance level of 5% is equal to (2,776). Thus the price t count> t table (12.176> 2.776) it is proved that the hypothesis there is no significant difference in the effect on the use of shampoo extract Gambir in both groups against dandruff scalp treatments with significance level of 5% was rejected. Meaning that there are significant with the use of shampoo extract Gambir against dandruff scalp care. For that is expected to respondents to always use Gambir Extract Shampoo in treating dandruff scalp.Keywords: Dandruff, Gambir extract shampo.